Leveling up: along-level diffusion tensor imaging in the spinal cord of multiple sclerosis patients - Witt, Atlee A.; Combes, Anna J. E.; Sweeney, Grace; Prock, Logan E.; Houston, Delaney; Stubblefield, Seth; McKnight, Colin D.; O’Grady, Kristin P.; Smith, Seth A.; Schilling, Kurt G. (Frontiers in Neuroimaging, 2025)
IntroductionMultiple sclerosis (MS) is a chronic neuroinflammatory disease marked by demyelination and axonal degeneration, processes that can be probed using diffusion tensor imaging (DTI). In the brain, white matter (WM) tractography enables anatomically specific analysis of microstructural changes. However, in the spinal cord (SC), anatomical localization is inherently defined by cervical levels, offering an alternative framework for regional analysis.MethodsThis study employed an along-level approach to assess both microstructural (e.g., fractional anisotropy) and macrostructural (e.g., cross-sectional area) features of the SC in persons with relapsing-remitting MS (pwRRMS) relative to healthy controls (HCs).ResultsCompared to conventional whole-cord averaging, along-level analyses provided enhanced sensitivity to group differences. Detailed segmentation of WM tracts and gray matter (GM) subregions revealed spatially discrete alterations along the cord and within axial cross-sections. Notably, while GM atrophy was associated with clinical disability, microstructural changes did not exhibit significant correlations with disability measures.DiscussionThese findings underscore the utility of level-specific analysis in detecting localized pathology and suggest a refined framework for characterizing SC alterations in MS.